2014
DOI: 10.1016/j.cub.2014.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Activity-Dependent Structural Plasticity of Perisynaptic Astrocytic Domains Promotes Excitatory Synapse Stability

Abstract: SummaryBackground: Excitatory synapses in the CNS are highly dynamic structures that can show activity-dependent remodeling and stabilization in response to learning and memory. Synapses are enveloped with intricate processes of astrocytes known as perisynaptic astrocytic processes (PAPs). PAPs are motile structures displaying rapid actin-dependent movements and are characterized by Ca 2+ elevations in response to neuronal activity. Despite a debated implication in synaptic plasticity, the role of both Ca 2+ e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
316
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 303 publications
(338 citation statements)
references
References 61 publications
10
316
1
Order By: Relevance
“…Astrocytes respond to sensory inputs or synaptic activity with intracellular Ca 2+ rises and remodeling of perisynaptic astrocytic processes, resulting in the release of neuroactive substances that may not only acutely affect synaptic and neuronal activity, but may also result in slower and more chronic aspects of neuronal plasticity (23,(51)(52)(53)(54)(55). Indeed, slower astrocyte-neuron interaction is more consistent with the temporal dynamics of astrocytic Ca 2+ waves, which are much slower than the rapid time course of synaptic transmission (53).…”
Section: Methodsmentioning
confidence: 99%
“…Astrocytes respond to sensory inputs or synaptic activity with intracellular Ca 2+ rises and remodeling of perisynaptic astrocytic processes, resulting in the release of neuroactive substances that may not only acutely affect synaptic and neuronal activity, but may also result in slower and more chronic aspects of neuronal plasticity (23,(51)(52)(53)(54)(55). Indeed, slower astrocyte-neuron interaction is more consistent with the temporal dynamics of astrocytic Ca 2+ waves, which are much slower than the rapid time course of synaptic transmission (53).…”
Section: Methodsmentioning
confidence: 99%
“…Very fine, and apparently highly mobile, astrocytic processes have been reported in organotypic brain slices using a membrane‐bound GFP (Benediktsson et al, 2005). Furthermore, co‐labeling of dendritic spines and PAPs in hippocampal (Halassa et al, 2007a; Perez‐Alvarez et al, 2014; Verbich et al, 2012) and cerebellar slices (Lippman Bell et al, 2010; Lippman et al, 2008) as well as in vivo (Bernardinelli et al, 2014b; Perez‐Alvarez et al, 2014) suggested that PAPs are highly dynamic structures that engage and disengage with dendritic spines, also responding to the induction of synaptic plasticity (Bernardinelli et al, 2014b; Perez‐Alvarez et al, 2014). …”
Section: Current Methods To Monitor Fine Astrocyte Morphology: Promismentioning
confidence: 99%
“…Astrocytes (and probably PAPs) express both, AMPARs and mGluRs (see above) and both receptor types might be involved in astrocytic filopodia outgrowth (Bernardinelli et al, 2014a). More recently, the induction of LTP in hippocampal slices and whisker stimulation has led to measureable PAP displacement in the hippocampus and the barrel cortex, respectively (Bernardinelli et al, 2014b; Perez‐Alvarez et al, 2014). It was suggested that PAP motility is (a) synapse‐specific, (b) neuronal activity‐dependent (application of TTX blocks PAP movement), (c) mGluR‐dependent, (d) Ca 2+ ‐dependent, and (e) IP 3 ‐dependent (Bernardinelli et al, 2014b; Perez‐Alvarez et al, 2014).…”
Section: Triggering Structural Plasticity Of Astroglia By Excitatory mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study showed that the motility of perisynaptic astrocytic processes that enveloped dendritic spines correlated with spine coverage and promoted spine stability in the mouse somatosensory cortex after whisker stimulation. 61 Another study showed that a blockade of astrocytic glutamate uptake accelerated experience-dependent spine elimination during development. 62 Microglia has also been found to closely interact with spines.…”
Section: Structural Plasticity Of Dendritic Spinesmentioning
confidence: 99%